2016
DOI: 10.1007/s00381-016-3268-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term mortality rates in pediatric hydrocephalus—a retrospective single-center study

Abstract: Mortality in hydrocephalic pediatric patients is high especially in the first postoperative years but is even significant in adult patients with pediatric hydrocephalus. As deaths occur even after 20 years, routine follow-up of long-term survivors remains necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 32 publications
1
23
2
3
Order By: Relevance
“…23 In our series, mortality was 9%, similar to that described in the study by Srihawan et al 9 Such variability is mostly influenced by 2 factors: the type of patients predominating in each series (those with a higher percentage of patients with CNS tumors show higher rates), and series with a high prevalence of resistant Gram-negative bacilli. 21,22 In the study by Gmeiner et al, 2 who analyzed the causes of death in the long term in patients with ventricular CSF shunts, 78% of related deaths were caused by an infection and not by a shunt and short-circuit dysfunction. This was consistent with the study by Tuli et al, 24 who assessed 907 pediatric patients (children with CNS tumors were excluded) and concluded that a short-circuit-associated infection was a predictor of death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 In our series, mortality was 9%, similar to that described in the study by Srihawan et al 9 Such variability is mostly influenced by 2 factors: the type of patients predominating in each series (those with a higher percentage of patients with CNS tumors show higher rates), and series with a high prevalence of resistant Gram-negative bacilli. 21,22 In the study by Gmeiner et al, 2 who analyzed the causes of death in the long term in patients with ventricular CSF shunts, 78% of related deaths were caused by an infection and not by a shunt and short-circuit dysfunction. This was consistent with the study by Tuli et al, 24 who assessed 907 pediatric patients (children with CNS tumors were excluded) and concluded that a short-circuit-associated infection was a predictor of death.…”
Section: Discussionmentioning
confidence: 99%
“…5 Mortality has been reported to be variable but, in general, low, although recent publications have described a mortality rate higher than 15%. 2,6 Few pediatric studies have been conducted that assess the factors associated with mortality in this type of infections.…”
Section: Original Articlementioning
confidence: 99%
“…Although BM is initially managed medically, unsuccessful or untimely treatment can result in sequelae, such as postinfectious hydrocephalus and subdural empyema, which can require neurosurgical intervention. 64 Global efforts to better characterize the transmission patterns of BM in endemic regions are ongoing. 6,30,136…”
Section: Bacterial Meningitismentioning
confidence: 99%
“…1 0 , 1 8 , 2 1 Existen estudios que reportan prevalencias mayores, como el trabajo de, Bathia et al (15%), 12 Kanik et al (15,8%), 10 23 La mortalidad en nuestra serie fue del 9%, similar al estudio de Srihawan et al 9 Esta variabilidad se ve influenciada, mayormente, por dos factores: el tipo de pacientes que predomina en cada serie (aquellas series con mayor porcentaje de pacientes con tumores del SNC presentan tasas más altas), junto con las series que presentan alta prevalencia de bacilos Gram-negativos resistentes. 21,22 En el estudio de Gmeiner et al, 2 quienes analizaron las causas de muerte a largo plazo en pacientes con SDV-LCR, el 78% de las muertes relacionadas fueron por infección y no por disfunción del corto circuito y sistema, lo que coincidió con el trabajo de Tuli et al, 24 que evaluaron 907 pacientes pediátricos (excluyeron a los niños con tumores del SNC) y concluyeron que la infección asociada al corto circuito fue un predictor de muerte.…”
Section: Discussionunclassified
“…5 La mortalidad reportada es variable, en general, baja, aunque existen publicaciones recientes con una mortalidad mayor del 15%. 2,6 Hay pocos estudios en pediatría que evalúen los factores asociados a la mortalidad en este tipo de infecciones.…”
Section: Artículo Originalunclassified